The Neurobehavioral Pharmacology of Ketamine: Implications for Drug Abuse, Addiction, and Psychiatric Disorders - Trujillo, Keith A. (ILAR J, 2011)
Ketamine was developed in the early 1960s as an anesthetic and has been used for medical and veterinary procedures since then. Its unique profile of effects has led to its use at subanesthetic doses for a variety of other purposes: it is an effective analgesic and can prevent certain types of pathological pain; it produces schizophrenia-like effects and so is used in both clinical studies and preclinical animal models to better understand this disorder; it has rapid-acting and long-lasting antidepressant effects; and it is popular as a drug of abuse both among young people at dance parties and raves and among spiritual seekers. In this article we summarize recent research that provides insight into the myriad uses of ketamine. Clinical research is discussed, but the focus is on preclinical animal research, including recent findings from our own laboratory. Of particular note, although ketamine is normally considered a locomotor stimulant at subanesthetic doses, we have found locomotor depressant effects at very low subanesthetic doses. Thus, rather than a monotonic dose-dependent increase in activity, ketamine produces a more complex dose response. Additional work explores the mechanism of action of ketamine, ketamine-induced neuroadaptations, and ketamine reward. The findings described will inform future research on ketamine and lead to a better understanding of both its clinical uses and its abuse.